Fresh fish supplier / Akmal Zaki Nordin ... [et al.] - Akmal Zaki, Nordin; Mohd Sahrul Fahmy, Muhamad Hanif; Mohd Shukri, Md Saad; Ahmad Hazeeq, Ahmad Hisham; Mohd Hafiz Hakimi, Zahkai (Faculty of Electrical Engineering, 2006)
We have decided to establish a company that consists of five (5) shareholders. Each of them is appointed base on their experience and skill such as General Manager, Operation Manager, Administration & Financial, Marketing and Sales Executive. The purpose of choosing the business is to produce the good fresh water fish. This is because the people must have a good nutrient for their life to make sure their have a good life and healthy. For our proposal is to help arry entrepreneur as a guideline to the organization in order to execute any business's activity.Beside that, it is using to convice certain party for instance the bank in order to give a business's loan. As a measure in determining either the business is profitable or else.